1997
DOI: 10.1074/jbc.272.46.29113
|View full text |Cite
|
Sign up to set email alerts
|

Two Hepatic Enhancers, HCR.1 and HCR.2, Coordinate the Liver Expression of the Entire Human Apolipoprotein E/C-I/C-IV/C-II Gene Cluster

Abstract: We show that the liver-specific expression of all four genes in the human apolipoprotein (apo) E/C-I/C-IV/C-II gene cluster in transgenic mice is determined by the coordinate action of two distinct hepatic control regions (HCR). These enhancers are positioned 15 kilobases (kb) (HCR.1) and 26 kb (HCR.2) downstream of the apoE gene. To investigate the action of each HCR, transgenic mice were generated with a 70-kb human genomic fragment that contained the complete apoE gene cluster or with this fragment modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 55 publications
2
72
0
Order By: Relevance
“…The coregulation of closely linked genes through shared sequence elements in cis (such as enhancers, repressors, insulators, locus control and matrix attachment regions, etc.) has been described for gene families such as apoE, ␣-globin, ␤-globin, Hox genes, and others (49)(50)(51)(52). Similarly, our expression data identified the proximal Serpin subcluster as linked and differentially regulated genes.…”
Section: Discussionmentioning
confidence: 56%
“…The coregulation of closely linked genes through shared sequence elements in cis (such as enhancers, repressors, insulators, locus control and matrix attachment regions, etc.) has been described for gene families such as apoE, ␣-globin, ␤-globin, Hox genes, and others (49)(50)(51)(52). Similarly, our expression data identified the proximal Serpin subcluster as linked and differentially regulated genes.…”
Section: Discussionmentioning
confidence: 56%
“…Through a series of elegant studies using transgenic mouse models, Taylor and coworkers (21)(22)(23)47) demonstrated that the HCRs control the expression of all four genes in the liver, whereas the 620-bp MEs direct the expression of apoE in multiple tissues (24 -26). However, the role of ME.1 and ME.2 in controlling the expression of apoC-I, apoC-IV and apoC-II in specific tissues has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of apoE expression has been extensively studied in transfected cells (Reardon et al, 1986;Smith et al, 1988;García et al, 1996;Harris et al, 2004b) and in transgenic mice (Shachter et al, 1993;Simonet et al, 1993;Allan et al, 1995Allan et al, , 1997Shih et al, 2000;Grehan et al, 2001a,b;Zheng et al, 2004) expressing apoE genomic or cDNA constructs. Although these systems have provided valuable information, practical considerations have limited systematic study of apoE expression.…”
Section: Introductionmentioning
confidence: 99%